POLA PERENCANAAN DAN STRATEGI PEMBANGUNAN WISATA ALAM BERKELANJUTAN SERTA BERWAWASAN LINGKUNGAN - Anak Agung Gde Djaja Bharuna S (Bumi Lestari Journal of Environment, 2009)
The background of this study was our concern on the sustainability of the environment wich was an asset for tourism. For nature-based and nature-related tourisms, maintaining of nature attraction which was the main focus point for tourism was an important agenda. The destruction of the environment would reduce its attractiveness and as a result would change its reputation as a tourist destination. Nature-based and nature-related tourisms tended to have unique values, and recently more tourists had an interest in nature. Easy and good accessibility and the presence of potential markets contributed to the development of these types of tourist attractions which then uncontrolled developed into mass tourism. In other to maintain the environment, it was important to find out wether the strategic plan for tourism development had a concern to the sustainability of the environment. Some cases of nature-based tourism development had made environment to damage as tourists’ visit might cause decrease int the species diversity, erosion, pollution, contamination and decreased visual landscaping quality. Very often, the gradation had already reached decreasing phase of ’survivorship’ of nature, which would influenced onto the environment quality. As a result the visitors would feel uncomfortable to visit this destination anymore. This was because of there was no integrated management yet established, especially between economic and ecologic visions in taking decision on planning and on the strategy tourism development processes. In order to keep the sustainability of the environment, which minimizing the negative impacts, this article was written to find out planning and strategy on sustainable development of nature-based tourism. The method of writing this article was utilizing literature review and also some continuing research.